2004
DOI: 10.1007/s00442-004-1549-8
|View full text |Cite
|
Sign up to set email alerts
|

Host-parasitoid extinction and colonization in a fragmented prairie landscape

Abstract: Few field studies of natural populations have examined the factors influencing local extinctions and colonization of empty habitat patches for a prey species and its predator. In this study, I carried out a census of planthopper (Prokelisia crocea; Hemiptera: Delphacidae) and egg parasitoid (Anagrus columbi; Hymenoptera: Mymaridae) incidence and densities in 147 host-plant patches (Spartina pectinata; Poaceae) over seven planthopper generations in a tall-grass prairie landscape. For both species, the likelihoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 52 publications
5
54
0
Order By: Relevance
“…3). This increase in parasitoid persistence with patch size was also found in the field (Cronin 2004) and can be explained by the spatial structure that the oscillating host-parasitoid populations develop in a single patch. In this case, a threshold area is needed to sustain the typical spatial wave-like or chaotic pattern.…”
Section: Discussionmentioning
confidence: 82%
“…3). This increase in parasitoid persistence with patch size was also found in the field (Cronin 2004) and can be explained by the spatial structure that the oscillating host-parasitoid populations develop in a single patch. In this case, a threshold area is needed to sustain the typical spatial wave-like or chaotic pattern.…”
Section: Discussionmentioning
confidence: 82%
“…Besides food webs, several examples from other multitrophic systems give an indication of how antagonistic host-parasitoid networks may be affected by fragmentation (Cronin, 2004;Kruess, 2003;Thies et al, 2005 Figure 18 Impacts of habitat fragmentation caused by drought in experimental stream food webs: results from a long-term field experiment in artificial streams Ledger et al, 2008Ledger et al, , 2009Ledger et al, , 2011. Drought can have patchy effects in river networks and individual stream channels can be viewed as fragmented patches in the wider riverscape.…”
Section: Antagonistic Host-parasitoid Networkmentioning
confidence: 99%
“…Most grassland habitats have been fragmented to some extent. Recent studies have shown that leafhopper species are affected by the effects of fragmentation, especially reduced habitat area, small habitat patches being associated with an increased risk of local extinction for many species (Biedermann 2000;Cronin 2004). In a review of existing studies on leafhopper populations in fragmented landscapes, Biedermann (2002) found that a high proportion of species were area-sensitive.…”
Section: Fragmentation and Habitat Lossmentioning
confidence: 99%
“…However, species differ widely in their response to habitat fragmentation (Biedermann 2004), some species being only marginally affected, whilst others require large areas for persistence. Furthermore, the import effect of habitat connectivity on the occurrence and persistence of grassland leafhopper species has been highlighted (Biedermann 2002;Cronin 2004). …”
Section: Fragmentation and Habitat Lossmentioning
confidence: 99%